The impact of energy crisis on the meat production profitability - Rodica Chetroiu; Lidia Iurchevici (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The purpose of this paper is to evaluate the impact that energy crisis which has debuted in 2022, had on the level of beef, pork and poultry meat production profitability. The methods used in the study are comparative analyzes of the evolution of some technical-economic and profitability indicators, calculated for the years 2018 and 2022. The research results show that indicators such as variable expenses, energy and fuel expenses, fixed expenses, production cost, the different income rates, etc., recorded higher values in 2022 compared to 2018, in some of them even by more than 50%, and the economic results obtained by farmers went from profit to loss. In conclusion, the impact of the energy crisis in the period under study was a negative one, demanding for carrying out the activity flows, affecting the entire meat production sector.
Keywords: Q12; Q13; 330; impact; meat; energy crisis; profitability